Medium-concentration electrolyte suitable for extremely cold environment, preparation method and lithium metal soft package battery
By using medium concentration electrolyte in lithium-ion batteries, the viscosity and solvation ability of the electrolyte are adjusted, the problem of energy and power density loss of lithium-ion batteries under low temperature conditions is solved, and the high capacity retention rate of lithium-metal batteries in extremely cold environments is achieved.
Patent Information
- Application Number
- CN202411952394.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-14
AI Technical Summary
Lithium-ion batteries exhibit energy and power density losses under low temperature conditions, and the low temperature performance of lithium-metal batteries is affected by problems such as increasing electrolyte viscosity, limited lithium-ion transmission capacity and unstable electrode/electrolyte interface.
A medium-concentration electrolyte is used, consisting of lithium salt, carbonate solvent and diluent. By vacuum drying and molecular sieve removal treatment, the lithium salt concentration and the ratio of solvent to diluent are adjusted, the viscosity and solvation ability of the electrolyte are reduced, the side reactions are inhibited, and the rapid transmission of lithium ions is promoted.
In extremely cold environments, the wetting and oxidation stability of the electrolyte are improved, the migration capacity of lithium ions is enhanced, and the low-temperature discharge capacity retention rate of lithium metal batteries reaches 50.98%, significantly improving the performance of the battery in extreme environments.
Smart Images

Figure CN119627228A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium batteries, and in particular relates to a medium-concentration electrolyte and a lithium metal soft-pack battery suitable for extremely cold environments. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life and no memory effect, and have been widely used in various fields of national economy and national defense construction. However, when the battery is operated at a temperature below -30°C, commercial graphite-based lithium-ion batteries will suffer serious energy and power density losses due to slow reaction kinetics. For traditional Panasonic 18650 lithium-ion batteries, only 5% of the energy density can be maintained at -40°C. The problem of capacity attenuation at low temperatures has become one of the main obstacles limiting its application in high-altitude areas and certain military and aviation fields.
[0003] Replacing graphite with lithium metal, which has an extremely high specific capacity (3860 mAh / g), has become one of the effective strategies to improve the energy density of batteries and a promising technical solution for low-temperature operating devices. However, the poor interfacial transfer kinetics of lithium ions and the growth of lithium dendrites under low temperature conditions have affected the application of lithium metal batteries. As an important component of the battery, the electrolyte is the medium for ion transport. It determines the mobility of ions, the solvation structure of lithium ions, and the composition and structure of the electrode / electrolyte interface film, and is a key factor affecting the electrochemical performance of the battery. When the battery operates at a lower temperature, the viscosity of the electrolyte increases or even solidifies, resulting in a decrease in the ion migration rate and conductivity, making its wettability to the electrode and separator worse, and increasing the solid-liquid interface resistance between the electrode and the electrolyte; in addition, the desolvation energy barrier of lithium ions increases, which is not conducive to the transport of lithium ions, and ultimately leads to the performance degradation of lithium metal batteries. In addition to electrode structure design and surface modification, electrolyte engineering plays a key role in improving the low-temperature performance of lithium metal batteries.
[0004] High-concentration electrolytes, fluorinated electrolytes, locally high-concentration electrolytes, weakly solvated electrolytes, etc. have been developed, but there are still many problems. They cannot solve the problems of low and rapid attenuation of battery capacity under low temperature conditions and dendrite growth, unstable electrode / electrolyte interface, and volume expansion of lithium metal negative electrodes. Summary of the invention
[0005] In view of the above problems, the present invention provides a medium-concentration electrolyte and a lithium metal soft-pack battery suitable for extremely cold environments, aiming to improve the oxidation stability of the electrolyte and the low-temperature discharge capacity of the lithium metal battery. By providing a medium-concentration electrolyte, the overall solvation capacity of the electrolyte can be reduced, the interaction between the solvent in the electrolyte and the transition metal cations dissolved from the positive electrode surface can be inhibited, the occurrence of side reactions can be reduced, and the rapid transmission of lithium ions can be achieved.
[0006] To achieve the above object, the present invention proposes the following technical solutions: A medium-concentration electrolyte suitable for an extremely cold environment, the electrolyte consisting of a lithium salt, a solvent and a diluent.
[0007] The lithium salt is vacuum dried for 12-24 h, and the solvent or diluent is dehydrated using 4A molecular sieve. The molecular sieve treatment process is as follows: the molecular sieve is placed in a muffle furnace, dried at 300° C. for 12 h, and then naturally cooled to no less than 150° C. and transferred to a glove box.
[0008] The lithium salt is one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium bis(fluorosulfonyl)imide, 2,2-dimethyl-1,3-dioxane-5-carboxylate lithium, and 2,2-difluoro-4,5-dioxo-1,3,2-dioxaborate lithium. These lithium salts have one or more characteristics of easy dissociation, high ionic conductivity or low charge transfer resistance.
[0009] The solvent is one of dimethyl carbonate, diphenyl carbonate, bis(4-nitrobenzene) carbonate and ethylene carbonate.
[0010] The diluent is one of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, ethoxy(pentafluoro)cyclotriphosphazene, trimethyl phosphate, succinonitrile and 1,2-difluorobenzene.
[0011] The lithium salt concentration is 1-2 mol / L.
[0012] The preferred lithium salt concentration is 1.2-1.5 mol / L.
[0013] The molar ratio of the solvent to the diluent is 1:0.5-3.
[0014] The preparation method of the medium-concentration electrolyte comprises the following steps: at room temperature, in a glove box filled with an argon protective atmosphere, dissolving the lithium salt in a solvent, stirring under magnetic conditions, adding a diluent after mixing evenly, continuing magnetic stirring, mixing evenly and standing for 8-24 hours to obtain a medium-concentration electrolyte suitable for an extremely cold environment.
[0015] The oxygen content of the argon gas is less than 0.1 ppm, and the water content is less than 0.1 ppm.
[0016] A lithium metal soft pack battery comprises a positive electrode, a negative electrode and a medium concentration electrolyte, wherein the positive electrode is a nickel-cobalt-manganese layered oxide (LiNi 0.8 Mn 0.1 Co 0.1O2), the negative electrode is 50μm lithium metal, and the diaphragm is a composite diaphragm made of PP / PE / PP.
[0017] The beneficial effects of the present invention are: (1) When the battery is working under low temperature conditions, the viscosity of the high-concentration electrolyte increases as the temperature decreases, and the lithium ion transmission capacity is limited. The present invention introduces a diluent based on the ester high-concentration electrolyte, which reduces the viscosity of the electrolyte, improves the wettability of the electrolyte under low temperature conditions, improves the oxidation stability of the electrolyte, reduces solvent coordination, and increases the ion diffusion rate; further, by adjusting the ratio of the solvent and the diluent, the free solvent molecules are reduced, and the solvation structure of the system is regulated. This diluent does not coordinate with lithium ions, but is evenly distributed in the lithium ion solvation structure, prompting more anions to enter the first solvation sheath of lithium ions, weakening the interaction between lithium ions and solvents, promoting the rapid desolvation of lithium ions under low temperature conditions and enhancing the migration ability of lithium ions; in addition, the preferential decomposition of anions forms an inorganic component-rich SEI, which improves the stability of the lithium metal negative electrode, promotes the transfer of charge on the interface, and improves the performance of lithium metal batteries at low temperatures. This method greatly reduces the cost of the electrolyte.
[0018] (2) The electrolyte-matched lithium metal battery provided by the present invention can achieve a capacity retention rate of up to 50.98% at ultra-low temperatures (-60°C), which is of great significance for the application of batteries in extreme environments such as the deep sea and outer space. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 (a) is the cycle performance of the Li / NMC811 battery of Example 1 and the comparative example at -40°C, and 1(b) is the charge and discharge curve of the Li / NMC811 battery of Example 1 at -40°C; Figure 2 (a) and (b) are discharge curves of the Li / NMC811 battery of Example 1 at -50°C and -60°C, respectively; Figure 3 (a) is the cycle performance of the Li / NMC811 battery of Example 2 and the comparative example at -40°C, and 3(b) is the charge and discharge curve of the Li / NMC811 battery of Example 2 at -40°C; Figure 4 (a) is the cycle performance of the Li / NMC811 battery of Example 3 and the comparative example at -40°C, and (b) is the charge and discharge curve of the Li / NMC811 battery of Example 3 at -40°C; Figure 5 The cycle performance of the Li / NMC811 soft pack battery of Example 2 at -40°C; DETAILED DESCRIPTION
[0020] The raw materials used in the present invention were purchased from Suzhou Duoduo Chemical Technology Co., Ltd., Hubei Rongbai Lithium Battery Material Co., Ltd., Sinopharm Chemical Reagent Co., Ltd. and Dongguan Kelude Experimental Equipment Technology Co., Ltd.
[0021] In the following examples, 2016-type button cells were used to assemble button cells, and a lithium copper composite tape with a thickness of 50 μm was selected as the negative electrode in the lithium metal battery, with a loading of 4 or 10 mg / cm 2 LiNi 0.8 Mn 0.1 Co 0.1 O2 (NMC811) is the positive electrode, the diaphragm is a 20μm thick PP / PE / PP diaphragm, and the electrolyte consumption for each battery is 100μL.
[0022] The lithium metal soft pack battery uses a 50 μm thick lithium strip as the negative electrode and a loading of 10 mg / cm 2 LiNi 0.8 Mn 0.1 Co 0.1 O2 (NMC811) is used as the positive electrode, and the diaphragm is a 20 μm thick PP / PE / PP diaphragm.
[0023] The difference between each group of examples and comparative examples is whether a diluent is added, and the difference between the examples is the ratio of the solvent to the diluent.
[0024] Comparative Example A high-concentration electrolyte, the raw materials are lithium salt and solvent; the lithium salt is lithium bis(fluorosulfonyl)imide (LiFSI), the molar concentration is 5.5 mol / L, and the solvent is dimethyl carbonate. Weigh 1.028896 g of lithium bis(fluorosulfonyl)imide, and weigh 1 mL of dimethyl carbonate based on the lithium salt concentration of 5.5 mol / L. The preparation method is: In a glove box filled with argon atmosphere, a certain amount of lithium salt was dissolved in dimethyl carbonate, and the mixture was stirred magnetically and evenly mixed, and then allowed to stand overnight to obtain a comparative example.
[0025] The electrolyte was used for Li / NMC811 battery cycle performance test, the test conditions are: at 25 ° C, at a constant current rate of 0.1C (1C = 200 mA / g) charged to 4.35 V, and then at a constant current rate of 0.1C discharged to 2.7 V, after 4 cycles, again at a constant current rate of 0.1C charged to 4.35 V, in a fully charged state at -40 ° C discharged to 2.7 V at 0.1C, and then charged to 4.35 V at 0.1C again, after constant voltage charging at 4.35 V to a current less than 0.05C, at 0.1C discharged to 2.7 V, for performance testing.
[0026] Example 1 A medium-concentration electrolyte, the raw materials are lithium salt, solvent and diluent; wherein: the lithium salt is lithium bis(fluorosulfonyl)imide (LiFSI), and the molar concentration is 1.4 mol / L. The solvent is dimethyl carbonate. The diluent is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE). The molar ratio of the solvent to the diluent is 2.2:3. Weigh 0.262 g of lithium bis(fluorosulfonyl)imide, and according to the lithium salt concentration of 1.4 mol / L and the molar ratio of the solvent to the diluent of 2.2:3, weigh 290 microliters of dimethyl carbonate and 710 microliters of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether. The preparation method is: in a glove box filled with argon atmosphere, dissolve the lithium salt in dimethyl carbonate, add the diluent TTE after magnetic stirring to mix evenly, mix evenly and let stand overnight to obtain a medium-concentration electrolyte.
[0027] The electrolyte was used for the Li / NMC811 battery cycle performance test. The test conditions were: at 25°C, the battery was charged to 4.35 V at a constant current rate of 0.1C (1C = 200 mA / g), then discharged to 2.7 V at a constant current rate of 0.1C. After 4 cycles, the battery was charged to 4.35 V at a constant current rate of 0.1C again. In the fully charged state, the battery was discharged to 2.7 V at 0.1C at -40°C, then charged to 4.35 V at 0.1C again. After charging at 4.35 V at a constant voltage until the current was less than 0.05C, the battery was discharged to 2.7 V at 0.1C. The test results are as follows: Figure 1 At -40℃, the matching loading is 10 mg / cm 2 The initial discharge capacity of the battery with NMC811 positive electrode is 154.9 mAh / g. After 35 cycles, the discharge capacity is 111.4 mAh / g. In addition, the matching loading of 4 mg / cm 2 The discharge capacity of the battery with NMC811 positive electrode at -50℃ and -60℃ is as follows Figure 2 At -50℃, the initial discharge capacity is 123.44 mAh / g, and the capacity retention rate is as high as 60.2% of room temperature; at -60℃, the initial discharge capacity is 104.5 mAh / g, and the capacity retention rate is as high as 50.98% of room temperature.
[0028] Example 2 The same as Example 1, except that the molar ratio of the solvent to the diluent is 1: 1. Weigh 0.262 g of lithium bis(fluorosulfonyl)imide, based on a lithium salt concentration of 1.4 mol / L and a molar ratio of the solvent to the diluent of 1: 1, weigh 360 μl of dimethyl carbonate and 640 μl of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
[0029] The electrolyte was used for the Li / NMC811 battery cycle performance test. The test conditions were: at 25°C, the battery was charged to 4.35 V at a constant current rate of 0.1C, and discharged to 2.7 V at a constant current rate of 0.1C. After 4 cycles, the battery was charged to 4.35 V at a constant current rate of 0.1C again. In the fully charged state, the battery was discharged to 2.7 V at 0.1C at -40°C, and then charged to 4.35 V at 0.1C again. After charging at 4.35 V at a constant voltage until the current was less than 0.05C, the battery was discharged to 2.7V at 0.1C. The test results are as follows: Figure 3 As shown. At -40℃, the initial discharge capacity is 165.6 mAh / g, and after 35 cycles, the discharge capacity is 154.9 mAh / g. The 2 Ah lithium metal soft pack battery in Example 2 is matched, and the test results are as follows Figure 5 As shown, at -40°C, its initial discharge capacity is 1.5 Ah.
[0030] Example 3 The same as Example 1, except that the ratio of solvent to diluent is 3:2.2. Weigh 0.262 g of lithium bis(fluorosulfonyl)imide, based on a lithium salt concentration of 1.4 mol / L and a molar ratio of solvent to diluent of 3:2.2, weigh 430 μl of dimethyl carbonate and 570 μl of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
[0031] The electrolyte was used for the Li / NMC811 battery cycle performance test. The test conditions were: at 25°C, the battery was charged to 4.35 V at a constant current rate of 0.1C, and discharged to 2.7 V at a constant current rate of 0.1C. After 4 cycles, the battery was charged to 4.35 V at a constant current rate of 0.1C again. In the fully charged state, the battery was discharged to 2.7 V at 0.1C at -40°C, and then charged to 4.35 V at 0.1C again. After charging at 4.35 V at a constant voltage until the current was less than 0.05C, the battery was discharged to 2.7V at 0.1C. The test results are as follows: Figure 4 At -40℃, the initial discharge capacity is 96.1 mAh / g, and after 35 cycles, the discharge capacity is 132.6 mAh / g.
[0032] Example 4 The same as Example 1, except that the ratio of solvent to diluent is 1:0.5. Weigh 0.262 g of lithium bis(fluorosulfonyl)imide, based on a lithium salt concentration of 1.4 mol / L and a molar ratio of solvent to diluent of 1:0.5, weigh 527 μl of dimethyl carbonate and 473 μl of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
[0033] Example 5 The same as Example 1, except that the ratio of the solvent to the diluent is 1:3. Weigh 0.262 g of lithium bis(fluorosulfonyl)imide, based on a lithium salt concentration of 1.4 mol / L and a molar ratio of the solvent to the diluent of 1:3, weigh 156 μl of dimethyl carbonate and 844 μl of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
[0034] Example 6 The same as Example 1, except that the lithium salt concentration is 1 mol / L, and the ratio of the solvent to the diluent is 1:1. Weigh 0.1871 g of lithium bis(fluorosulfonyl)imide, based on the lithium salt concentration of 1 mol / L and the molar ratio of the solvent to the diluent of 1:1, weigh 360 microliters of dimethyl carbonate and 640 microliters of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
[0035] Example 7 The same as Example 1, except that the lithium salt concentration is 2 mol / L, and the ratio of the solvent to the diluent is 1:1. Weigh 0.3742 g of lithium bis(fluorosulfonyl)imide, based on the lithium salt concentration of 2 mol / L and the molar ratio of the solvent to the diluent of 1:1, weigh 360 microliters of dimethyl carbonate and 640 microliters of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
Claims
1. A medium concentration electrolyte suitable for extremely cold environments, characterized by: The electrolyte consists of lithium salt, solvent and diluent.
2. The medium concentration electrolyte according to claim 1, characterized in that: The lithium salt is vacuum dried, and the solvent or diluent is dehydrated using a molecular sieve.
3. The medium concentration electrolyte according to claim 1, characterized in that: The lithium salt is one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium bis(fluorosulfonyl)imide, lithium 2,2-dimethyl-1,3-dioxane-5-carboxylate, and lithium 2,2-difluoro-4,5-dioxo-1,3,2-dioxaborate.
4. The medium concentration electrolyte according to claim 1, characterized in that: The solvent is one of dimethyl carbonate, diphenyl carbonate, bis(4-nitrobenzene) carbonate and ethylene carbonate.
5. The medium concentration electrolyte according to claim 1, characterized in that: The diluent is one of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, ethoxy(pentafluoro)cyclotriphosphazene, trimethyl phosphate, succinonitrile and 1,2-difluorobenzene.
6. The medium concentration electrolyte according to claim 1, characterized in that: The lithium salt concentration is 1-2 mol / L.
7. The medium concentration electrolyte according to claim 6, characterized in that: The lithium salt concentration is 1.2-1.5 mol / L.
8. The medium concentration electrolyte according to claim 1, characterized in that: The molar ratio of the solvent to the diluent is 1:0.5-3.
9. A method for preparing the medium-concentration electrolyte according to any one of claims 1 to 8, comprising the following steps: Under room temperature conditions, in a glove box filled with argon protective atmosphere, the lithium salt is dissolved in the solvent, stirred under magnetic conditions, and the diluent is added after mixing evenly. The magnetic stirring is continued, and the mixture is allowed to stand for 8-24 hours after mixing evenly to obtain a medium-concentration electrolyte suitable for extremely cold environments.
10. A lithium metal soft pack battery, characterized in that: It comprises a positive electrode, a negative electrode and the medium-concentration electrolyte according to any one of claims 1 to 8, wherein the positive electrode is a nickel-cobalt-manganese layered oxide, the negative electrode is lithium metal, and the diaphragm is a composite diaphragm made of PP / PE / PP.
Citation Information
Patent Citations
Low-concentration lithium ion battery electrolyte and lithium ion battery prepared from same
CN114024036A
Local high-concentration low-temperature electrolyte and preparation method thereof
CN114899493A
Localized high salt concentration electrolyte
WO2024145180A2
Localized high salt concentration electrolyte
WO2024145182A2
Lithium secondary battery
WO2024228487A1